Removal of Sulfamethazine by a Fe⁰-Na₂S₂O₈ System - Habibi, Enric; How, Javier; Montero-Mora, Anthony (Journal of Green Energy and Environmental Engineering, 2024)
This study investigates the rapid degradation of sulfamethazine (SM2) in water by adding micron-sized zero-valent iron (Fe⁰) to catalyze sodium persulfate (PS) for generating substantial sulfate radicals (SO₄•⁻). The effects of ZVI particle size, Fe⁰ dosage, PS concentration, initial pH, and reaction temperature on SM2 degradation efficiency were examined. Results indicated that within a certain range, the degradation efficiency of SM2 increased with smaller ZVI particle size, higher Fe⁰ dosage, and increased PS concentration. In the Fe⁰-PS system, complete degradation of SM2 was achieved under conditions of Fe⁰ dosage = 0.25 g/L, PS concentration = 7.5 mmol/L, and SM2 concentration = 50 μmol/L. The initial pH and reaction temperature significantly influenced SM2 degradation, with optimal performance observed at pH = 5 and a temperature of 45°C. The Fe⁰-PS system not only effectively removed SM2 but also demonstrated good removal efficiency for Chemical Oxygen Demand (COD) .